Patient and caregiver involvement in the formulation of guideline questions: findings from the European Academy of Neurology guideline on palliative care of people with severe multiple sclerosis. (9th September 2018) - Köpke, S.; Giordano, A.; Veronese, S.; Christin Rahn, A.; Kleiter, I.; Basedow‐Rajwich, B.; Fornari, A.; Battaglia, M. A.; Drulovic, J.; Kooij, L.; Koops, J.; Mens, J.; et al.
Abstract : Background and purpose: Patient and public involvement in clinical practice guideline development is recommended to increase guideline trustworthiness and relevance. The aim was to engage multiple sclerosis (MS) patients and caregivers in the definition of the key questions to be answered in the European Academy of Neurology guideline on palliative care of people with severe MS. Methods: A mixed methods approach was used: an international online survey launched by the national MS societies of eight countries, after pilot testing/debriefing on 20 MS patients and 18 caregivers, focus group meetings of Italian and German MS patients and caregivers. Results: Of 1199 participants, 951 (79%) completed the whole online survey and 934 from seven countries were analysed: 751 (80%) were MS patients (74% women, mean age 46.1) and 183 (20%) were caregivers (36% spouses/partners, 72% women, mean age 47.4). Participants agreed/strongly agreed on inclusion of the nine pre‐specified topics (from 89% for 'advance care planning' to 98% for 'multidisciplinary rehabilitation'), and <5% replied 'I prefer not to answer' to any topic. There were 569 free comments: 182 (32%) on the pre‐specified topics, 227 (40%) on additional topics (16 guideline‐pertinent) and 160 (28%) on outcomes. Five focus group meetings (three of MS patients, two of caregivers, and overall 35 participants) corroborated the survey findings. In addition, they allowed an explanation of the guideline production process and the exploration of patient‐important outcomes and of taxing issues. Conclusions: Multiple sclerosis patient and caregiver involvement was resource and time intensive, but rewarding. It was the key for the formulation of the 10 guideline questions and for the identification of patient‐important outcomes.